A Comparison of Implementation Curriculum 13 and Merdeka Policies In Inclusive Early Childhood Education - Dyah Rufiandri (SEA-CECCEP, 2023)
This research compares the policy of implementing curriculum 13 with the merdeka curriculum at the inclusive early childhood education level. teacher readiness, infrastructure facilities, teacher training that supports and the readiness of the government system. The method used is a literature review. The results of the research are that there is no readiness of schools and teachers, as well as policies that are still undergoing improvement. Otherwise, the result of this research is that it can contribute insight and knowledge about the competencies aimed at in the 2013 curriculum and the merdeka curriculum which can be seen from the basic competencies in the 2013 curriculum and Learning Achievements in the merdeka curriculum for early childhood care education (ECCE).